Desingularization of Black Hole Space-Times (Bulletin of Pure and Applied Sciences – Physics, 2023)
The desingularization of a class of black hole space-times arising as solutions to the  string equations is considered in connection with the consistency of the quantum  theory and the description of nonperturbative states with quantum numbers from the  particle spectrum. The geometry arising in an extreme limit of one of the singular  solutions to the gravitational field equations is demonstrated to be a background of N =  2 string theory. The positivity of the masses in the particle spectrum is proven through  quasilocal integrals near the resolved singularities in these limits of black hole  space-times.